Mechanisms affecting the speed and direction of vacuum arc cathode spots movement in a magnetic field - Vasyliev, V.V.; Strel’nitskij, V.E. (Problems of Atomic Science and Technology, 2023)
Based on the known experimental and theoretical data, a new model of the plasma jet, which emit by cathode spot (СS) along the magnetic field proposed. According to this model, the plasma jet contains an oppositely directed current of accelerated ions of the cathode material with an excess positive charge and a current of accelerated electrons with an excess negative charge, between which an electric field of polarization of the plasma jet formed. Based on this model, the basic parameters of the plasma jet from the external parameters of the magnetic field, the arc current, and the average charge state of the ions calculated. The main mechanisms affecting the speed and direction of movement of the arc CS on the cathode end surface clarified for the first time. На основі відомих експериментальних і теоретичних даних запропонована нова модель плазмового струменя, який емітує катодні плями (КП) вздовж магнітного поля. Згідно цієї моделі він містить протилежно направлені струм прискорених іонів матеріалу катода з надлишковим позитивним зарядом і струм прискорених електронів з надлишковим негативним зарядом, між якими утворюється електричне поле поляризації плазмового струменя. На основі цієї моделі вперше виконані розрахунки основних параметрів плазмового струменя від зовнішніх параметрів магнітного поля, струму дуги та середнього зарядового стану іонів у плазмовому струмені. Вперше з’ясовані основні механізми, що впливають на швидкість і напрямок руху КП дуги по поверхні торця катода, що випаровується.